anonymous
  • anonymous
Functions! Please help, very important! :) (file attached)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
slaaibak
  • slaaibak
f . g = h f = 3x + 5 h = 3x^2 + 3x + 2 so f(g(x)) = 3x^2 + 3x + 2 That means: 3(g(x)) + 5 = 3x^2 + 3x + 2 By inspection: g(x) = x^2 + x - 1
anonymous
  • anonymous
what's inspection, sorry?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

slaaibak
  • slaaibak
Figuring it out by looking at it
anonymous
  • anonymous
I don't follow, how you get this part? 3(g(x)) + 5 = 3x^2 + 3x + 2
slaaibak
  • slaaibak
we know h(x) = 3x^2 + 3x +2 --------> (1) and we know f.g = f(g(x)) but f(x) = 3x + 5, therefore f(g(x)) = 3(g(x)) + 5 --------> (2) and we know that f.g = h ----> f(g(x)) = h(x) therefore: (1) = (2) 3(g(x)) + 5 = 3x^2 + 3x +2
anonymous
  • anonymous
ohkay, and then you can kinda just look at it and like guess and check and see that x^2+x-1 works for g, right?
slaaibak
  • slaaibak
Yes. Or you can just solve G like a normal variable: 3(g(x)) + 5 = 3x^2 + 3x +2 Substract 5 on both sides: 3(g(x)) = 3x^2 + 3x -3 Divide by 3: g(x) = x^2 + x - 1
anonymous
  • anonymous
oh! that's much clearer. thank you so much!
slaaibak
  • slaaibak
shot
anonymous
  • anonymous
shot?
slaaibak
  • slaaibak
haha, colloquial for "cool, no problem"

Looking for something else?

Not the answer you are looking for? Search for more explanations.